Midrange Unmanned Autonomous Watercraft for Search and Rescue - Catane, Ephrem Joseph A.; Gabutin, Leary G.; Tamosa, Krishna Carla V.; Aliac, Chris Jordan G.; Lauron, Roel B. (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose – The maritime sector is a crucial industry in shaping the Philippine economy, yet it is plagued by a high rate of accidents and fatalities. To address these challenges, this study explores the integration of unmanned technologies into maritime Search and Rescue (SAR) operations. Method – This research explores using a low-cost USV for SAR in the Philippines. Analyzing various unmanned options (ROVs, AUVs), the study focused on an affordable USV design. Built with readily available materials and open-source software, the USV prioritizes stability, real-time data collection (sensors, camera), and remote control for operator intervention. Rigorous testing evaluated its performance and functionality. Results – Testing yielded promising results: the USV autonomously navigated waypoints and transmitted clear video and sensor data.  However, these tests revealed limitations in GPS accuracy and telemetry range likely due to the controlled setting. Further evaluation in real-world environments is necessary. Conclusion – The proposed USV design shows promising potential as a mid-range SAR platform. The successful completion of autonomous waypoint navigation and the functionality of various sensors demonstrate the USV's capabilities. However, further testing in more complex environments is crucial to assess its real-world effectiveness, particularly regarding GPS accuracy and communication reliability. Recommendations – Based on the findings, the study recommends several areas for improvement. Optimizing the telemetry range through higher power configurations or alternative communication protocols is essential. Additionally, integrating object identification technology would significantly enhance search efficiency. Implementing additional measures like Real-Time Kinematic (RTK) correction systems could improve GPS accuracy. Finally, further testing of Ardupilot's fail-safe mechanisms for GPS loss is recommended. Research Implications – This research shows promise for low-cost USVs in the Philippine SAR.  The design can aid PCG in developing affordable SAR technology to save lives.